The initiation and maintenance of gonadotropin-releasing hormone neuron identity in congenital hypogonadotropic hypogonadism - Chung, Wilson CJ; Tsai, Pei-San (Frontiers in Endocrinology, 2023)
Neurons that secrete gonadotropin-releasing hormone (GnRH) drive vertebrate reproduction. Genetic lesions that disrupt these neurons in humans lead to congenital hypogonadotropic hypogonadism (CHH) and reproductive failure. Studies on CHH have largely focused on the disruption of prenatal GnRH neuronal migration and postnatal GnRH secretory activity. However, recent evidence suggests a need to also focus on how GnRH neurons initiate and maintain their identity during prenatal and postnatal periods. This review will provide a brief overview of what is known about these processes and several gaps in our knowledge, with an emphasis on how disruption of GnRH neuronal identity can lead to CHH phenotypes.